Kesulitan pengambilan keputusan karier pada siswa di daerah rural: Bagaimana peran dukungan sosial? - Fadhillah, Samirah Hasna; Yudiana, Whisnu (Persona:Jurnal Psikologi Indonesia, 2020)
AbstractThe process of making decisions about careers by students tends to make them difficult, especially for students in rural areas. The perception of social support obtained from the environment namely, parents, teachers, classmates, and close friends are the things that may help students make a career decision. This study conducted to explore the relationship between perceived social support and career decision-making difficulties junior high school students in a rural area. Two measurement instruments used namely Child and Adolescent Social Support Scale (CASSS) and Career Decision Making Difficulties Questionnaire (CDDQ). In the CASSS, there are two scales, values, and frequency. Data collected from 9th-grade junior high school students in the rural area (n= 242) with multistage cluster sampling techniques. The results of the study used the Spearman correlation test showed that the perception of social support value from parents and teachers is negatively correlated with difficulty in making career decisions. In contrast, the frequency scale of social support from classmates and close friends resulted in a positive relationship. The more frequent students get social support, the more difficult for them to make a decision. In conclusion, social support helped the student to decrease their career decision-making difficulties. However, the frequencies of the support have not higher than their expectation. Keywords:  Career decision making difficulties, Junior high school students, Perceived social support, Rural AbstrakProses pengambilan keputusan karier yang dilakukan siswa cenderung membuatnya kesulitan, terutama siswa di daerah rural. Persepsi dukungan sosial dari lingkungan sekitar yaitu, orang tua, guru, teman sekelas dan teman dekat adalah salah satu hal yang dapat membantu siswa membuat keputusan karier. Penelitian dilakukan untuk melihat hubungan persepsi dukungan sosial dari keempat sumber dengan kesulitan pengambilan keputusan karier siswa kelas 9 daerah rural. Terdapat dua alat ukur yang digunakan yaitu, Child and Adolescent Social Support Scale (CASSS) dan Career Decision Making Difficulties Questionnaire (CDDQ). CASSS membagi dua skala dalam alat ukurnya, skala value dan frekuensi. Pengambilan data dilakukan pada siswa kelas 9 daerah rural (n = 242), dengan teknik multistage cluster sampling. Hasil penelitian menggunakan uji korelasi spearman menunjukkan persepsi value dukungan sosial orang tua dan guru berkorelasi negatif dengan kesulitan pengambilan keputusan karier, sedangkan skala frekuensi dukungan sosial teman sekelas dan teman dekat berkorelasi positif. Semakin sering siswa mendapatkan dukungan sosial, semakin sulit dalam membuat keputusan. Sebaliknya, jika siswa memiliki value yang lebih tinggi untuk dukungan sosial, semakin rendah kesulitan pengambilan keputusan kariernya. Secara umum dapat disimpulkan, pada dasarnya dukungan sosial dapat menurunkan kesulitan pengambilan keputusan. Hanya saja, frekuensi dukungan yang diberikan tidak boleh melebihi apa yang dibutuhkan oleh Individu.Kata kunci:  Kesulitan pengambilan keputusan karier; Persepsi dukungan sosial; Rural; Siswa Sekolah Menengah Pertama